2022
DOI: 10.18332/tid/155007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on smoking (waterpipe and cigarette) and participants' BMI across various sociodemographic groups in Arab countries in the Mediterranean Region

Abstract: INTRODUCTION Tobacco smokers are at high risk of developing severe COVID-19. Lockdown was a chosen strategy to deal with the spread of infectious diseases; nonetheless, it influenced people's eating and smoking behaviors. The main objective of this study is to determine the impact of the COVID-19 lockdown on smoking (waterpipe and cigarette) behavior and its associations with sociodemographic characteristics and body mass index. METHODS The data were derived from a large-scale retrospective cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Overall, 16 studies were found to be related to obesity among adults within the studied time frame (8 studies in the West Bank, two studies in the Gaza Strip, and five national studies) ( 89 104 ). Abdeen and his colleagues found that the prevalence of overweight in the West Bank was 35.5% among women and 40.3% among men, while obesity was 31.5% in women and 17.5% in men ( 89 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 16 studies were found to be related to obesity among adults within the studied time frame (8 studies in the West Bank, two studies in the Gaza Strip, and five national studies) ( 89 104 ). Abdeen and his colleagues found that the prevalence of overweight in the West Bank was 35.5% among women and 40.3% among men, while obesity was 31.5% in women and 17.5% in men ( 89 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, most of the participants surveyed were particularly sedentary, spending long periods sitting or watching TV. Similarly, a survey conducted among 10 Arab countries (Bahrain, Egypt, Jordan, Kuwait, Lebanon, Oman, Palestine, Qatar, Saudi Arabia, and the United Arab Emirates), stated that within the UAE moderate activity levels decreased from 37.9% pre-lockdown to 34.3% during lockdown and high activity levels decreased from 15.8% pre-lockdown to 9.9% during lockdown (Al Sabbah et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a survey in the US reported that among cigarette smokers, 33% stated an increase in their habits due to increased stress caused by the pandemic, with 23% reporting an increase in e-cigarette use (Kalkhoran et al, 2022). On the contrary, in 10 Arab countries in the Middle East, the average smoking rate decreased by 24% during lockdown (Al Sabbah et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations